The Nesting Success of the Indian Shag Phalacrocorax fuscicollis (Aves: Suliformes: Phalacrocoracidae) in the Kamlanehru Zoological Park, Ahmedabad, India - PATEL, NIKITA; THAKKER, ROHAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
The Indian shag Phalacrocorax fuscicollis is a freshwater species that has been nesting in the Kamlanehru Zoological Park (KZP), Ahmedabad since 2019. Here, the breeding of the Indian shag was studied during the period of 2021 to record the nesting success of species in KZP. The breeding activities of the Indian shag commenced in July and continued until November. It was noted that the birds built their nests on (Azadirachta indica, Ficus religiosa and Peltophorum pterocarpum) trees. As recorded both partners participated in nest building but male recorded while collecting most of materials. Incubation period was from 28-30 days and fledging period recorded upto 8 weeks. Though many studies were recorded of cormorants and breeding biology of little cormorants received major attention. Here, In particular, there no published information on the nesting success of Indian shag recorded. To support this information gap, this study was conducted to record the observations of successful nesting of Indian shag. Site observations and photographs of Indian shag nesting since 2019 were used to compile a record of successful breeding and compared with the present observations.